A Modulator‐Induced Defect‐Formation Strategy to Hierarchically Porous Metal–Organic Frameworks with High Stability. Issue 2 (8th December 2016) - Cai, Guorui; Jiang, Hai‐Long
Abstract: The pore size enlargement and structural stability have been recognized as two crucial targets, which are rarely achieved together, in the development of metal–organic frameworks (MOFs). Herein, we have developed a versatile modulator‐induced defect‐formation strategy, in the presence of monocarboxylic acid as a modulator and an insufficient amount of organic ligand, successfully realizing the controllable synthesis of hierarchically porous MOFs (HP‐MOFs) with high stability and tailorable pore characters. Remarkably, the integration of high stability and large mesoporous property enables these HP‐MOFs to be important porous platforms for applications involving large molecules, especially in catalysis. Abstract : Cause and defect : Pore size enlargement and structural stability are two crucial targets but hardly achieved together in metal–organic frameworks (MOFs). A versatile modulator‐induced defect‐formation strategy has been developed to provide hierarchically porous MOFs (HP‐MOFs) with high stability and tailorable pore characters, which are important porous platforms for large‐molecule applications, especially in catalysis.